Expanding the tools for identifying mononuclear phagocyte subsets in swine: Reagents to porcine CD11c and XCR1. (December 2016) - Deloizy, Charlotte; Bouguyon, Edwige; Fossum, Even; Sebo, Peter; Osicka, Radim; Bole, Angélique; Pierres, Michel; Biacchesi, Stéphane; Dalod, Marc; Bogen, Bjarne; Bertho, Nicolas; Schwartz-Cornil, Isabelle
Abstract: Pig is a domestic species of major importance in the agro-economy and in biomedical research. Mononuclear phagocytes (MNP) are organized in subsets with specialized roles in the orchestration of the immune response and new tools are awaited to improve MNP subset identification in the pig. We cloned pig CD11c cDNA and generated a monoclonal antibody to pig CD11c which showed a pattern of expression by blood and skin MNP subsets similar to humans. We also developed a porcine XCL1-mCherry dimer which specifically reacted with the XCR1-expressing dendritic cell subset of the type 1 lineage in blood and skin. These original reagents will allow the efficient identification of pig MNP subsets to study their role in physiological and pathological processes and also to target these cells in novel intervention and vaccine strategies for veterinary applications and preclinical evaluations. Highlights: Improvement of pig dendritic cell (DC) subset identification in pig. Generation of an anti-pig CD11c mAb and pig XCL1-mCherry vaccibody. CD11c and XCL1 expression pattern in DC subsets is similar between pigs and humans.